Model-Based Decision Support System for Improving Emergency Response. Issue 3 (7th February 2023) - Nagarajan, Meenakshi; Ganapathy, Subhashini; Cheatham, Michelle
Abstract: A Mobile-Based Ontology Integrated Decision Support System was built in an effort to improve the transparency in disaster situations. Using hypothetical chemical hazard scenarios, the decision-making accuracy and time taken by incident commanders using the Incident Command System was compared to incident commanders without the use of the system. The existing design of incident command systems limits the ability to manage workload and results in a limited span of knowledge. Sixteen firefighters were tested using the mobile-based ontology integrated decision support system. The results discussed in this study indicate that the information presented by the decision support system significantly improved commander's decision-making. Potential applications of this research include Strengthening disaster risk reduction and management capacity through improved preparedness; Advancing regional and national initiatives for disaster response and risk reduction; and providing the foundation for future policies and procedures that can be easily implemented within the ICS framework.